DINÂMICA DA COBERTURA FLORESTAL NO MUNICÍPIO DE CRISSIUMAL-RS DURANTE UM PERÍODO DE VINTE ANOS - Lippert, Diogo Belmonte; Benedetti, Ana Caroline; Pereira, Rudiney Soares (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705543 The present study aims to assess the dynamics of forest cover in Crissiumal-RS, throughremote sensing techniques. From the digital classification of satellite images from Landsat 5 TMsensor, between 1988 and 2008 were generated thematic maps use and land cover on therespective dates. These maps were later crossed through the Space for GIS Algebraic Language(LEGAL), which allowed determination of the following processes: maintaining forest, forestregeneration and deforestation. Among the main results is the increase in forest cover in 4756.33ha and also the occurrence of 1508.04 ha of deforestation at the end of the period. The increase inforest cover may be combined with declining rural population and the abandonment of areaspreviously occupied by agriculture to comply with the law.